Strategy Management in Improving the Effectiveness of Higher Education Management - Mukhtar Mukhtar; Hidayat Hidayat; Surya Habibi (International Journal of Education, Information Technology, and Others, 2020)
This study aims to determine the Management of Higher Education Strategies in Improving the Effectiveness of PTKIS management in Jambi Province, to uncover the strategies carried out by PTKIS managers and to formulate, implement and evaluate strategies in increasing the effectiveness of PTKIS in Jambi Province. The results of the study that the strategic planning PTKIS in Jambi Province in increasing effectiveness is constrained by several factors as follows: Manager's misunderstanding in the implementation of strategic management, communication between managers and subordinates is not in line, not aligning strategic goals with actions taken, ideas and innovations are not supported by plans right, and passive management, and motivation of managers who only target personal gains versus shared goals.